2010
DOI: 10.1021/jp1047985
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Proof Superhydrophobic Films from Flexible Carbon Nanotube/Polymer Coatings

Abstract: In this paper, we report a simple and inexpensive method for fabricating stable superhydrophobic films from flexible carbon nanotube (CNT)/polymer coatings. The CNT/polymer coatings, which do not contain any fluorinated compounds, maintain their superhydrophobicity after bending and pressing and display excellent environmental stability. Furthermore, these superhydrophobic films can be coated onto glass, metals, and polymers, resulting in water-repellent, self-cleaning surfaces exhibiting high water contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Recently, they were used to create surface roughness so as to impart super-repellent properties to the resultant surfaces. 26 27 demonstrated that superamphiphobic surface could be obtained perfluorosilanerendered TiO 2 /single-walled carbon nanotube composite coatings. Interestingly, the wetting ability of such coatings could be tuned from superoleophobic to superoleophilic via ultraviolet 40 irradiation.…”
Section: Functionalization With Nanoparticles (Np)mentioning
confidence: 99%
“…Recently, they were used to create surface roughness so as to impart super-repellent properties to the resultant surfaces. 26 27 demonstrated that superamphiphobic surface could be obtained perfluorosilanerendered TiO 2 /single-walled carbon nanotube composite coatings. Interestingly, the wetting ability of such coatings could be tuned from superoleophobic to superoleophilic via ultraviolet 40 irradiation.…”
Section: Functionalization With Nanoparticles (Np)mentioning
confidence: 99%
“…This has proved very effective and is very simple. 49 An interesting variation on this has been to coat cotton fibers with carbon nanofibers with a polymer linkage. 50 This has shown good properties against washing and similar surfaces have resisted hot water, 51 factors often causing problems for superhydrophobic textiles.…”
Section: Other Fiber Surfacesmentioning
confidence: 99%
“…Wettability is one of the primary surface properties of solid materials, which is normally characterized by measurement of the contact angle of a surface [1][2][3]. Generally, surfaces with water contact angles larger than 150°and slide angles lower than 10°are called superhydrophobic surfaces [4,5].…”
Section: Introductionmentioning
confidence: 99%